1992
DOI: 10.1111/j.1751-0813.1992.tb07502.x
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor effects in sheep of alkaloids identified in Australian Tribulus terrestris

Abstract: Fresh, mature, ungrazed Tribulus terrestris plant material was subjected to a standard alkaloid extraction procedure. The extract was fractionated by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). Two major alkaloid fractions were demonstrated. These fractions were identified by means of TLC, ultraviolet spectrofluorimetry (UVS) and HPLC, as the beta-carboline indoleamines harmane and norharmane. The extractable alkaloid content was determined to be 44 mg/kg dry matter. Synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 9 publications
0
37
0
1
Order By: Relevance
“…Indole alkaloids, containing an intact β-carboline skeleton such as norharmane, are of widespread natural occurrence. Norharmane, the simplest example of β-carbolines, has been described to occur naturally in some higher plants (Gramineae, Sapotaceae and Zygophyllaceae) (Allen & Holmstedt, 1980;Bourke et al, 1992) and rarely for marine organisms, such as the dinoflagellate Noctiluca miliaris (Inoue et al, 1980). Larsen et al (1994) described the isolation of three chlorine-containing β-carbolines (the so-called bauerines A-C) from the cyanobacterium Dichotrix baueriana.…”
Section: Discussionmentioning
confidence: 99%
“…Indole alkaloids, containing an intact β-carboline skeleton such as norharmane, are of widespread natural occurrence. Norharmane, the simplest example of β-carbolines, has been described to occur naturally in some higher plants (Gramineae, Sapotaceae and Zygophyllaceae) (Allen & Holmstedt, 1980;Bourke et al, 1992) and rarely for marine organisms, such as the dinoflagellate Noctiluca miliaris (Inoue et al, 1980). Larsen et al (1994) described the isolation of three chlorine-containing β-carbolines (the so-called bauerines A-C) from the cyanobacterium Dichotrix baueriana.…”
Section: Discussionmentioning
confidence: 99%
“…11,16) Earlier studies showed that T. terrestris L. contained flavanoids, steroid saponins, alkaloids and polysaccharides. [17][18][19][20][21][22] In our previous studies, we isolated from T. terrestris L. eight steroid saponins, TTS-8, TTS-9, TTS-10, TTS-11, TTS-12, TTS-13, TTS-14 and TTS-15.…”
Section: Discussionmentioning
confidence: 99%
“…Publications on TT have reported the isolation of several steroid saponins of furostanol type [15][16][17], with protodioscin as the most dominant one [12], as well as alkaloids and flavonoids [18][19][20][21][22], and recently new feruloyl amide derivative named as tribulusamide C [23]. Obreshova et al [15] identified protogracilin besides protodioscin as the dominate furostanol bisglycoside and, so these compounds are considered to be factor responsible for biological activity of products derived from this plant [14].…”
Section: Introductionmentioning
confidence: 99%